Status of Women in the Heian Period (794 –1185): A Study of the Literary Works of Murasaki Shikibu and Sei Shonagon - Kassim, Faezah; Jais, Abd Wahid (WILAYAH: The International Journal of East Asian Studies, 2014)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.